1990
DOI: 10.1213/00000539-199005000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Labetalol and Nitroprusside for Inducing Hypotension During Major Surgery

Abstract: The hemodynamic and intrapulmonary shunt effects of intravenous labetalol and nitroprusside were compared during induced hypotension for major spinal surgery. A randomized, double-blind protocol was used in which 20 patients, ASA physical status I or II, received either nitroprusside infusion (n = 10) or labetalol bolus injections of 10 mg every 10 min (n = 10) until mean arterial blood pressure was reduced to 55-60 mm Hg. Pulmonary artery pressures were measured and mixed venous samples obtained via a pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Hypotensive anaesthesia offers a dry surgical ®eld and may reduce blood loss and hence the need for transfusion [1,2]. Controlled hypotension is used in a variety of surgical procedures and several hypotensive agents are used [3]; however, sodium nitroprusside is the drug used most commonly for this purpose [4]. Sodium nitroprusside is a powerful vasodilator with a rapid onset and after stopping the infusion, arterial blood pressure returns rapidly to baseline values [5,6].…”
mentioning
confidence: 99%
“…Hypotensive anaesthesia offers a dry surgical ®eld and may reduce blood loss and hence the need for transfusion [1,2]. Controlled hypotension is used in a variety of surgical procedures and several hypotensive agents are used [3]; however, sodium nitroprusside is the drug used most commonly for this purpose [4]. Sodium nitroprusside is a powerful vasodilator with a rapid onset and after stopping the infusion, arterial blood pressure returns rapidly to baseline values [5,6].…”
mentioning
confidence: 99%
“…Presynaptic alpha-2 receptors are spared by labetalol so that the released norepinephrine can continue to inhibit further release of catecholamines via the negative feedback mechanism resulting from the stimulation of alpha-1 receptors. Moreover this drug targets 5-10 times more specific beta blockade 11,23 and prevent rebound hypertension and tachycardia. 20,10 Researchers used Labetalol and nitroprusside to induce hypotension in major surgeries and showed that nitroprusside significantly increased the heart rate but cardiac output remain unchanged with labetalol administration.…”
Section: Discussionmentioning
confidence: 99%
“…20,10 Researchers used Labetalol and nitroprusside to induce hypotension in major surgeries and showed that nitroprusside significantly increased the heart rate but cardiac output remain unchanged with labetalol administration. 11 The arterial hypertension is due to increase in cardiac output rather than increase in systemic vascular resistance. 22 We used low doses of fentanyl because larger dose may leads to muscular rigidity, bradycardia, and postoperative respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used in many surgical procedures, including radical prostatectomy [3,4]. The most commonly used drug to induce and maintain controlled hypotension is sodium nitroprusside (SNP) [3]. However, controlled hypotension may alter organ blood flow and tissue oxygenation [5].…”
Section: Introductionmentioning
confidence: 99%